Framework of Effective Risk Management in Small and Medium Enterprises (SMESs): a Literature Review - Nsikan Ekwere (Center for Economic Studies Universitas Katolik Parahyangan, 2016)
Governments have realised the need to encourage entrepreneurs to open small businesses believing that the development of the small business sector will decrease high unemployment rate thereby leading the country to a sustainable economic development. However, research shows that this aim cannot be achieved by only facilitating access to finance to entrepreneurs but that some management strategies such as risk management should be introduced, understood and applied by small business owners, in order for their businesses to go beyond the estimated survival period of three to five years. This paper reviews and provides background to which risk management techniques are applied within the ambit of small enterprises. The review shows that not many SME owners, managers, entrepreneurs or key designated employees effectively make use of a well-structured risk management tool and technique within their businesses, to achieve growth and sustainability.Keywords: Enterprise Risk Management, Small and Medium Enterprises (SMEs)